The Fork in the Road for Social Enterprises: Leveraging Moral Imagination for Long-Term Stakeholder Support - Brown, Jill A.; Forster, William R.; Wicks, Andrew C. (Entrepreneurship Theory and Practice, 2023)
Social enterprises (SEs) that receive early stakeholder support for their dual economic/social missions risk losing moral legitimacy when stakeholders assess them for social impact and find it lacking. We present a process model that begins at the “fork in the road” of stakeholder assessment and shows that when SEs continue to focus on primary stakeholders at the expense of secondary stakeholders impacted by the firm, they risk losing moral legitimacy and broader stakeholder support. Our model shows the process by which SEs can leverage their moral imagination and develop capabilities to generate long-term stakeholder support and sustained value creation.